2021
DOI: 10.3892/etm.2021.9982
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT1 in the resistance of HBV to IFN‑α

Abstract: The objective of the present study was to explore the mechanism of hepatitis B virus (HBV) resistance to interferon (IFN), and the role of signal transducer and activator of transcription 1 (STAT1). HepG2.2.15 cells were stimulated with a long-term (6-24 weeks) low-dose interferon (IFN)α-2b (10-70 IU/ml), so as to construct and screen a HepG2.2.15 cell model resistant to IFNα-2b. The changes of STAT1 and other proteins in the JAK-STAT signaling pathway, before and after drug resistance, were compared. The phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Specifically, there was a marked decrease in the phosphorylation of STAT1 in the IFNαresistant HepG2.2.15 cells, concomitant with a down-regulation in the expression of the 2′,5′-oligoadenylate synthetase 1. These findings suggest that disruptions in the JAK-STAT pathway, particularly reduced STAT1 phosphorylation, could support IFN-α treatment resistance observed in HBV patients (Xu et al, 2021) (Figure 3).…”
Section: The Interaction Of Hbx and Ifn Signal Pathway Regulation Of ...mentioning
confidence: 75%
“…Specifically, there was a marked decrease in the phosphorylation of STAT1 in the IFNαresistant HepG2.2.15 cells, concomitant with a down-regulation in the expression of the 2′,5′-oligoadenylate synthetase 1. These findings suggest that disruptions in the JAK-STAT pathway, particularly reduced STAT1 phosphorylation, could support IFN-α treatment resistance observed in HBV patients (Xu et al, 2021) (Figure 3).…”
Section: The Interaction Of Hbx and Ifn Signal Pathway Regulation Of ...mentioning
confidence: 75%
“…A number of studies have reported that IFN-α-2b can activate STAT1, resulting in the phosphorylation of STAT1 [30,31]. STAT1 is a member of STAT protein family.…”
Section: Discussionmentioning
confidence: 99%